A UAF1-containing multisubunit protein complex regulates the Fanconi anemia pathway. - Cohn, M; Kowal, P; Yang, K; Haas, W; Huang, T; Gygi, S; D'Andrea, A (2007)
The deubiquitinating enzyme USP1 controls the cellular levels of the DNA damage response protein Ub-FANCD2, a key protein of the Fanconi anemia DNA repair pathway. Here we report the purification of a USP1 multisubunit protein complex from HeLa cells containing stoichiometric amounts of a WD40 repeat-containing protein, USP1 associated factor 1 (UAF1). In vitro reconstitution of USP1 deubiquitinating enzyme activity, using either ubiquitin-7-amido-4-methylcoumarin (Ub-AMC) or purified monoubiquitinated FANCD2 protein as substrates, demonstrates that UAF1 functions as an activator of USP1. UAF1 binding increases the catalytic turnover (kcat) but does not increase the affinity of the USP1 enzyme for the substrate (KM). Moreover, we show that DNA damage results in an immediate shutoff of transcription of the USP1 gene, leading to a rapid decline in the USP1/UAF1 protein complex. Taken together, our results describe a mechanism of regulation of the deubiquitinating enzyme, USP1, and of DNA repair.